The Effect of Organizational Commitment and Job Satisfaction on the Performance of the State Civil Apparatus on the National Land Agency Bengkulu Province - Ayu Satriani; Oni Yulianti; Andriyani Prawitasari (Journal of Indonesian Management, 2021)
The results of the regression analysis show Y = 12.190 + 0.198X1 + 0.525 X2, this describes a positive regression direction, meaning that there is a positive influence between X1 (organizational commitment) and X2 (job satisfaction) on the performance (Y) of the State Civil Apparatus of the Provincial National Land Agency. Bengkulu. The value of the coefficient of determination is 0.419. This means that organizational commitment and job satisfaction affect the performance of the State Civil Apparatus of the Bengkulu Province National Land Agency by 41.9%, while the remaining 59.8% is influenced by other variables not examined in this study. Variable X1 (organizational commitment) shows a significance value of 0.038 <0.05. Because the significance value is less than 0.05, then X1 (organizational commitment) has a significant influence on the performance of (Y) State Civil Apparatus at the National Land Agency of Bengkulu Province. Variable X2 (job satisfaction) shows a significance value of 0.000 <0.05. Because the significance value is less than 0.05, then X2 (job satisfaction) has a significant effect on the performance of (Y) State Civil Apparatus at the National Land Agency of Bengkulu Province. The results of the F test at a significance level of 0.05 explains that organizational commitment and job satisfaction have a significant simultaneous influence on the performance of the State Civil Apparatus of the National Land Agency of Bengkulu Province..